2011
DOI: 10.3329/jhpn.v29i5.8904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Special Care Newborn Units in India

Abstract: The neonatal mortality rate in India is high and stagnant. Special Care Newborn Units (SCNUs) have been set up to provide quality level II newborn-care services in several district hospitals to meet this challenge. The units are located in some remotest districts where the burden of neonatal deaths is high, and access to special newborn care is poor. The study was conducted to assess the functioning of SCNUs in eight rural districts of India. The evaluation was based on an analysis of secondary data from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 20 publications
(28 reference statements)
3
56
1
Order By: Relevance
“…This study was shows that all 32(100%) NBCC were found partially functional as they were not follow five criteria for fully functional while in study chauhan et al in Bihar, India shows majority 39 (68.4%) of the NBCCs were partially functional and 5 (9%) NBCCs were nonfunctional at the time of the assessment. 10 This study revealed that some neonatal equipment were not available majority of health facility while in the study chauhan et al shows neonatal equipment were available and functional in most of the facilities and in study Neogi et al in Haryana, India shows Shortage of basic equipments and supplies at most of the special baby care units.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was shows that all 32(100%) NBCC were found partially functional as they were not follow five criteria for fully functional while in study chauhan et al in Bihar, India shows majority 39 (68.4%) of the NBCCs were partially functional and 5 (9%) NBCCs were nonfunctional at the time of the assessment. 10 This study revealed that some neonatal equipment were not available majority of health facility while in the study chauhan et al shows neonatal equipment were available and functional in most of the facilities and in study Neogi et al in Haryana, India shows Shortage of basic equipments and supplies at most of the special baby care units.…”
Section: Resultsmentioning
confidence: 99%
“…Pediatrician (20%) and MBBS medical officer (52%) were the least trained personnel on NSSK while in the study chauhan et al shows 66.4% medical officers, 72.7% SNs/ANMs, and 62.2% ancillary staff were trained. 10 In this study shows out of 101 health personnel, only 13 (14%) health care staff were able to provide proper resuscitation while chauhan et al revealed that 20% of the medical officers and 15% of the SNs/ANMs were not able to use essential newborn care equipment such as Ambu bag, radiant warmer, oxygen concentrator, and suction machine.…”
mentioning
confidence: 99%
“…This is also corroborated by evidence from another study. 26 The basic approach of the study is to train the staff with minimum academic qualification and motivation for involvement of the work. These staff are specially trained for care of LBW and VLBW babies and they are given responsibility of these babies and no other work so that they become dedicated newborn worker.…”
Section: Resultsmentioning
confidence: 99%
“…Neonates who require higher intensive care are referred to public sector specialty hospitals (teaching hospitals) or to private sector multispecialty hospitals. The first public SCNU was established in 2003, the resounding success of which has led to increased coverage to >150 districts; however, the actual number of beds is far less than what is required 2 12 13. A total of 507 SNCUs with 6408 beds were available across the country in late 2013 11 14.…”
Section: Levels Of Nicu Care In Indiamentioning
confidence: 99%
“…The ideal nurse–patient ratio is 1:1 for ventilated babies and 1:3–4 for all other babies 16. There is a serious concern of understaffing in both government and private sectors; an analysis has shown that only 50% of units were adequately staffed 13. Many trained doctors/nurses do not wish to take further training in neonatal care, and many trained ones go abroad for better remuneration and career growth.…”
Section: Manpower Infrastructure and Equipment Issues In Neonatal Camentioning
confidence: 99%